Baicalin modulates apoptosis via RAGE, MAPK, and AP-1 in vascular endothelial cells during Haemophilus parasuis invasion - Fu, Shulin (Innate Immun, 2019)
Glässer’s disease, caused by Haemophilus parasuis, is a chronic disease related to an inflammatory immune response. Baicalin exerts important biological functions. In this study, we explored the protective efficacy of treatment with baicalin and the potential mechanism of activation of the MAPK signaling pathway in porcine aortic vascular endothelial cells (PAVECs) induced by H. parasuis. H. parasuis stimulated expression of receptor for advanced glycation end products, induced a significant increase in the level of protein kinase-α and protein kinase-δ phosphorylation, and significantly up-regulated ERK, c-Jun N-terminal kinase, and p38 phosphorylation in PAVECs. H. parasuis also up-regulated the levels of apoptotic genes (Bax, C-myc, and Fasl) and the expression levels of c-Jun and c-Fos, and induced S-phase arrest in PAVECs. However, treatment with baicalin inhibited expression of RAGE, suppressed H. parasuis-induced protein kinase-α and protein kinase-δ phosphorylation, reduced ERK, c-Jun N-terminal kinase, and p38 phosphorylation, down-regulated apoptotic genes (Bax, C-myc, and Fasl), attenuated phospho-c-Jun production from the extracellular to the nuclei, and reversed S-phase arrest in PAVECs. In conclusion, baicalin treatment inhibited the MAPK signaling pathway, thereby achieving its anti-inflammatory responses, which provides a new strategy to control H. parasuis infection.